Ginekologija in perinatologija - Geršak, Ksenija (University of Maribor Press, 2025)
Second, revised and updated edition. Gynaecology and Perinatology. The textbook Gynaecology and Perinatology - second, revised and updated edition includes expert contributions from authors from the entire Slovenian field and renowned experts from abroad. The textbook is divided into 21 sections comprising 106 chapters. The textbook comprises chapters by 125 authors, written to a high professional standard, all of which have been critically reviewed by two referees. All the authors are internationally renowned experts in their fields, which gives the publication added weight and quality. The textbook is richly illustrated with the authors‘ own photographs and original drawings, and is accompanied by numerous tables. The rich content of the textbook will certainly be useful reading for all medical students and other health professionals working in the field of gynaecology and obstetrics, as well as for the general public.